Pengaruh Virtual Influencer Attractiveness, Humanlikeness, dan Credibility terhadap Purchase Intention pada Pengguna Media Sosial TikTok di DKI Jakarta (Studi Virtual Influencer Laverda Salsabila) - Salsabilla, Okta; Yohana, Corry; Kharismawan, Bagus (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of virtual influencer attractiveness, human-likeness, and credibility on purchase intention among TikTok social media users. This research employed a quantitative approach using a survey method. The sample consisted of 110 respondents selected through purposive sampling. The respondents were required to be 17–28 years old, reside in DKI Jakarta, have a TikTok account, be familiar with the virtual influencer Laverda Salsabila featured in this study, and have viewed Laverda Salsabila's promotional content on TikTok. Data were collected using a six-point Likert scale questionnaire and analyzed using IBM SPSS Statistics version 29. The findings indicate that, partially, the attractiveness variable has a positive and significant effect on purchase intention. The credibility variable also has a positive and significant effect on purchase intention. Meanwhile, the human-likeness variable does not have a significant effect on purchase intention.